PENGARUH HIPERREALITAS DALAM MEDIA SOSIAL TERHADAP GAYA HIDUP KONSUMTIF SISWA SMA NEGERI SE-KOTA PONTIANAK - Adhalia Zatalini; Yohanes Bahari; Rustiyarso Rustiyarso (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe title of this study is "The Effect of Hyperreality in Social Media on the ConsumptiveLifestyle of Public High School Students in Pontianak City". The purpose of this study isto describe the influence of hyperreality in social media on consumptive lifestyles thatoccur among state high school students in Pontianak City. The results of this study provethe use of social media supports activities, interests, and opinions in shaping andimproving the consumptive lifestyle of state high school students in Pontianak City.Hyperreality in social media also has a contribution in the daily lives of state high schoolstudents in Pontianak City. In the hypothetical test with a significance level of 5% of thetwo-party test and dk = 341 - 2 = 339, obtained thitung > ttabel (9,486 > 1,960) thenH1 is accepted and H0 is rejected. Furthermore, the correlation test rhitung= 0.458 withan alpha coefficient of 0.400 < R < 0.599 can be said to be quite strongly correlated.Based on the coefficient of determination and from the regression test output obtaineddetermination (R Square) of 0.210 with the understanding that hyperreality in socialmedia (X) affects consumptive lifestyle (Y) with a value of 21%, the rest is influenced byvariables not studied in this study.Keywords: hyperreality, social media, consumptive lifestyle